Institutional Constraints to Agriculture Development in Uganda - Bategeka, Lawrence; Kiiza, Julius; Kasirye, Ibrahim (Economic Policy Research Centre - EPRC, 2013)
Since the early 1990s, Uganda has implemented a number of reforms in the agricultural sector. However, in the past 10 years, the performance of the sector has lagged behind other sectors particularly services and industry. There are concerns among researchers and policy analysts that institutional constraints in agriculture play a central role in the lacklustre agricultural performance registered during the 2000s. This study examines the institutional constraints affecting agricultural production in Uganda. We recommend reforming the land tenure system as well as the architecture of the Ministry of Agriculture, Animal Industry and Fisheries as means of dealing with the major constraints.
Keywords: Institutional Constraints; Agriculture Development